2011
DOI: 10.1590/s0103-50532011000500018
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents from branches of Maytenus gonoclada (Celastraceae) and evaluation of antimicrobial activity

Abstract: Seis triterpenos pentacíclicos isolados dos galhos de Maytenus gonoclada (Celastraceae), incluindo todos os dados de RMN do novo composto 3-oxo-12α,29-diidroxifriedelano são aqui relatados. A estereoquímica do novo friedelano foi estabelecida por dados de RMN bidimensional (HSQC, HMBC e NOESY), e sua massa molecular confirmada por espectrometria de massas (ESI). Testes de atividade antimicrobiana usando método de difusão em disco e de macrodiluição foram realizados contra as bactérias Escherichia coli, Citroba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…A literature review was performed in order to obtain the 13 C NMR chemical shifts of the triterpenes from leaves and branches of M. gonoclada and M. robusta (OLIVEIRA et al, 2007;SILVA et al, 2011a;SILVA et al, 2011b;SILVA et al, 2013, NIERO et al, 2006SOUSA et al, 2012a;SOUSA et al, 2012b). The compounds (13 triterpenes for each species) were analyzed based on the chemical shifts of the carbon atoms C1 to C30, generating a matrix.…”
Section: Methodsmentioning
confidence: 99%
“…A literature review was performed in order to obtain the 13 C NMR chemical shifts of the triterpenes from leaves and branches of M. gonoclada and M. robusta (OLIVEIRA et al, 2007;SILVA et al, 2011a;SILVA et al, 2011b;SILVA et al, 2013, NIERO et al, 2006SOUSA et al, 2012a;SOUSA et al, 2012b). The compounds (13 triterpenes for each species) were analyzed based on the chemical shifts of the carbon atoms C1 to C30, generating a matrix.…”
Section: Methodsmentioning
confidence: 99%
“…H-28 (δ H 1.33) and it was consistent with a friedelane triterpene skeleton. 4,5,8 In the NOESY contour map, it was observed that the signal of H-18 (δ H 2.41) was correlated with the signals of H-12ax (δ H 3.98) and H-26 (δ H 1.22). The H-12 (δ H 3.98) showed correlations between the signals for H-25 (δ H 0.99) and H-26 (δ H 1.22), indicating that H-12 was in an axial position (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, friedelane triterpenes such as 3-oxofriedelane, 3β-hydroxyfriedelane, 3,11-dioxofriedelane, 3,16-dioxofriedelane, 3-oxo-12α-hydroxyfriedelane and 3-oxo-12α,29-dihydroxyfriedelane have been isolated from M. gonoclada. 4,5 Because of the range of pharmacological activities attributed to the triterpenes isolated from species of the Maytenus genus, 6,7 we studied the chloroform extract of branches of M. gonoclada in continuation of our investigation of bioactive compounds. A new friedelane triterpene, 3,16-dioxo-12α-hydroxyfriedelane 1, was isolated together with nine known compounds identified as 3,11-dioxofriedelane 2, 8 3,16-dioxofriedelane 3, 5,8 3,12dioxofriedelane 4, 9 3-oxo-12α,29-dihydroxyfriedelane 5, 5 3-oxofriedelane (friedelin) 6, 10 3β-hydroxyfriedelane 7, 11 3oxo-12α-hydroxyfriedelane 8, 4 3β-hydroxylup-20(29)-ene (lupeol) 9 8 and a mixture of long chain hydrocarbons 10 (Fig.…”
mentioning
confidence: 99%
“…Phytochemical studies of the Celastraceae family led to the isolation of many bioactive secondary metabolites such as flavonoids, steroids and different classes of pentacyclic triterpenes. Also, many reports describe pharmacological properties of triterpenes like anti-inflammatory, 6,7 antiulcerogenic, 8 analgesic, 9 antibacterial, antifungal, antiviral, antiparasitic, antioxidant, hepatoprotective, neuroprotective, insecticidal and others. 10 Moreover, some species are already employed in the treatments of gastric ulcers, presenting anti-inflammatory and analgesic activities such as Maytenus ilicifolia Mart.…”
Section: Introductionmentioning
confidence: 99%
“…The fractions C35-43 (CHCl 3 :EtOAc 85:15, 0.77 g) were submitted to a new CC (D, 78 fractions of the 15 mL) yielding 7 (5.2 mg) from the fraction D43 (CHCl 3 :EtOAc 98:2) and friedelan-1,3,21-trione (1) (535.0 mg) from the fractions D45-50 (CHCl 3 :EtOAc 85:15). The fractions B198-245 (CHCl 3 :EtOAc 80:20, 1.17 g) were re-chromatographed on silica gel CC (E, 81 fractions of the 15 mL) providing a mixture (467.6 mg) of 30-hydroxyfriedelan-3-one(8) and 21α-hydroxyfriedelan-3-one (9) from the fractions E40-44 (CHCl 3 :EtOAc 85:15). This mixture was purified on flash silica CC (F, 107 fractions of the 10 mL) yielding 8 (165.0 mg) from the fractions F64-67 (CHCl 3 :EtOAc 90:10).Part of the greenish solid from hexane leaf extract free of gutta (HLE) (14.0 g) was chromatographed on silica gel CC (G) furnishing 102 fractions of 200 mL.…”
mentioning
confidence: 99%